Method komresii images telecommunication systems based solution structural redundancy - Бараннік, Володимир Вікторович; Додух, Олександр Миколайович (Ukrainian Information Security Research Journal, 2013)
As a result of the conducted analysis of minimum time it is rotined on passing to videoinformacii, that for the existent and perspective systems of the aerospace monitoring with the use of side facilities of telecommunication it arrives at a few ten of minutes. It results in the obsolescence of the got information, acceptance of the belated and erroneous decisions. It is grounded, that for the decision of this problem it is suggested to utillize technologies of compression of videoinformation. It is rotined that existent technologies of compression on the basis of preliminary exposure of apertures, based on separate treatment of their constituents, that leads the decline of degree of compression of images. Forming of compact presentation of fragment of image is developed. Information technology of compression of images is created on the basis of the generalized encoding his coordinate-structural and line-by-line – scaling representations constituents. The construction of two-component encoding is developed on the basis of the first code constituent, formed on the basis of elements of line of array of approximating sizes, presented as an adaptive position number with unequal elements. Grounded, that is arrived at additional increase of degree of compression of images due to the exception of statistical surplus, decline of psikhovizual’noy surplus and reduction of structural surplus.